Role of Vibrations in Orthodontics: A Review - Goyal, Varun; Singh, Raj Kumar; Gupta, Nishant; Singh, Gurkeerat; Relhan, Ashima (Orthodontic Journal of Nepal, 2018)
Long treatment time has been a deterrent for the patients for pursuing orthodontic treatment. Orthodontist from time immemorial have been trying different methods for reducing the treatment time. It has been documented in literature that vibration therapy helps in bone remodelling and muscle regeneration as demonstrated in cases of osteoporosis, muscle loss and joint pain. Using the similar approach orthodontist from different era have tried to accelerate the tooth movement using different methods. This article summarises the efforts of different clinicians and their approaches to achieve reduced orthodontic treatment time as well as reducing the discomfort, pain and root resorption using pulsations and vibrations.